Information Technology Industry Buyers' Stock Performance in the Nordics: Evidence from 1995-2006 - Leino, Tuomas (My University, 2018)
In the end of 20th century the merger wave swept across the technological industry. Tens of thousands of mergers and acquisitions (M&A) were executed through the information technology industry and the technology companies’ stock prices were reaching all-time records. In many occasions the acquisition’s premiums were miserably overvalued and the acquirer paid significant overcompensation for the takeover target. The bubble was burst, and the information technology stocks became crashing down. The research problem of this thesis is to focus on identifying the explanatory factors that explain the performance differences between mergers executed during the Information technology pre-bubble and post-bubble situations. The empirical part is conducted in form of event study in which the acquirer merger performance is measured on short-and long-term time frame on Nordic data. Data period covers the time frame of 1995 up to until 2006 and the sample consists of 132 deals conducted by Nordic Technology firms. The merger performance is mirrored against the benchmark of other Nordic Technology firms which were not involved with transactions in the specified time period. The merger performance is measured with market model and buy-and hold abnormal returns. The review of previous literature indicates that the market structure and the unique quality of the products of information technology industry affect the strategic motives behind the merger strategy and to the valuation methods of the intangible assets. In the contrast with the findings of previous literature the acquisitions have the tendency to underperform the markets and the empirical results of the thesis are in line with previous research.
Keywords: Mergers; Acquisitions; Information Technology; Markets; Strategy; Intangible Assets; Valuation; Long-term performance; Short-term performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|